METODE PROFILE MATCHING MENENTUKAN PENERIMA BANTUAN PERBAIKAN RUMAH PADA KECAMATAN SIANTAR MARTOBA - Yurri Widya Paranthi (JURNAL ILMIAH INFORMATIKA, 2020)
Home Improvement Assistance in Siantar Martoba District is one of the government programs. The assessment process and decision making in this program is still subjective. The middle class people who have permanent jobs and have valuables thing such as motorbikes and television are still listed as a recipient of the Home Improvement Assistance. The application made in this research is a decision support system for recipients of home improvement assistance in Siantar Martoba district using the Profile Matching method.This application is used to help assess the competency of prospective recipients of home improvement assistance in Siantar Martoba and provide recommendations in decision making. The assessment criteria used include aspects of the state of the house and economic aspects. This profile matching method will compare the profiles of participants with ideal profiles of recipients of home improvement assistance. The smaller gap will make the opportunity to pass the assessment even greater. It is expected that the decision support system for recipients of home improvement assistance can help the government in determining prospective recipients entitled to help with housing repairs in Siantar Martoba with a faster, more accurate and effective assessment.